Tren Hijrah dan Dai Prematur: Analisis Fenomena Sosial dan Implikasinya dalam Dakwah Kontemporer - Harifah, Nurul (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The phenomenon of hijrah is increasingly popular among Indonesian urban communities, especially among the younger generation. However, this trend has also given rise to the phenomenon of "premature preachers," namely individuals who, with minimal understanding of religion, begin to give lectures or studies. This research aims to analyze this phenomenon through a qualitative approach with literature study and in-depth interviews. The research results show that the main motivation for hijrah is the search for spiritual identity, but this is often not accompanied by adequate deepening of religious knowledge. Premature Dai has the potential to provide a shallow understanding of religion and cause divisions in society. This article recommends the need for more structured religious guidance and education for individuals who have just emigrated.